2020
DOI: 10.1111/imcb.12420
|View full text |Cite
|
Sign up to set email alerts
|

Viperin binds STING and enhances the type‐I interferon response following dsDNA detection

Abstract: Viperin is an interferon‐inducible protein that is pivotal for eliciting an effective immune response against an array of diverse viral pathogens. Here we describe a mechanism of viperin’s broad antiviral activity by demonstrating the protein’s ability to synergistically enhance the innate immune dsDNA signaling pathway to limit viral infection. Viperin co‐localized with the key signaling molecules of the innate immune dsDNA sensing pathway, STING and TBK1; binding directly to STING and inducing enhanced K63‐l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…In addition to synthesizing ddhCTP, viperin interacts with a wide range of cellular and viral proteins. This extensive network of protein–protein interactions remains poorly understood but constitutes an equally important aspect of the enzyme’s antiviral properties. In many cases, it appears that viperin exerts its antiviral effects by facilitating the degradation of cellular and viral proteins important for viral replication .…”
mentioning
confidence: 99%
“…In addition to synthesizing ddhCTP, viperin interacts with a wide range of cellular and viral proteins. This extensive network of protein–protein interactions remains poorly understood but constitutes an equally important aspect of the enzyme’s antiviral properties. In many cases, it appears that viperin exerts its antiviral effects by facilitating the degradation of cellular and viral proteins important for viral replication .…”
mentioning
confidence: 99%
“…Organelle-organelle communication is critical for the transfer of proteins and lipids to fuel cellular events, and following detection of invading viral nucleic acid by sentinel innate immune receptors, important adaptor proteins within this pathway come together to form enhansosomes. Multiple proteins involved in the antiviral response have been shown to facilitate enhansosome formation with the LD as a platform, and it is possible that LD movement might facilitate this activity [25,26,47]. Additionally, recent work has demonstrated that LDs move away from mitochondrial contacts following detection of bacterial LPS by sentinel innate immune receptors, towards intracellular bacteria, facilitating a cellular anti-bacterial response, perhaps indicating that LD movement is critical following pathogen infection to ensure a good outcome for the host cell.…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation of LDs has been shown to drive an enhanced immune response in respect to viral infection, and to alter LD-mitochondrial interactions which underpin metabolic changes in the cell [21,23,24]. Additionally, it has recently been demonstrated that the LD resident protein, viperin, interacts with STING, likely on the Golgi and the ER, as well as TRAF6 and IRAK1 in the TLR7/9 pathways [25,26]. It is possible that the LD is involved in multiple organelle interactions that may facilitate and underpin a successful antiviral response following cellular infection.…”
Section: Introductionmentioning
confidence: 99%
“…The rest of DNA fragments with deletions of different regions of viperin, including the deletion of residues 9 to 42 (Δ9–42), 71 to 182 (Δ71–182) and 218 to 361 (Δ218–361), were amplified from the resulting full-length mouse viperin plasmid (p3xFLAG-viperin) and the amplicons then were digested with corresponding restriction enzymes, followed by ligation with p3xFLAG-CMV-14 vector linearized by Kpn I and Xba I enzymes. Human viperin-GFP-c1 or pGFP-c1 empty vector [ 33 ] was supplied by K. Helbig. Specific guide RNA targeting viperin (5′-CACCGTGTCATTAATCGCTTCAACG-3′ and 5′-AAACCGTTGAAGCGATTAATGACAC-3′) was inserted into a lentiCRISPR v2 vector containing mCherry coding sequence in the Th111I enzyme cutting site.…”
Section: Methodsmentioning
confidence: 99%